Modeling and simulation of minimum time-handling inverse dynamics of a vehicle. (July 2018) - Zhang, Li-Xia; Pan, Fu-Quan; Zhang, Hui; Feng, Ting
The performance of a vehicle in minimum time handling is highly important for the safety of the vehicle. In this study, a vehicle motion state equation with 3 degrees of freedom was established on the basis of the lateral, yaw, and longitudinal motions of the vehicle. Equations on the linear tire and motion trajectory were established with consideration of longitudinal load transfer to establish the vehicle-handling dynamics model. Steering-wheel angle, driving force equation set, and yaw angle equation had been introduced to convert the vehicle-handling dynamics model into the vehicle-handling inverse dynamics model. By introducing performance index, control set, and several constraint conditions, an optimal control model of the vehicle minimum time handling was established, which was solved by improved direct multiple-shooting nonlinear programming method. A comparison of the simulation results of ADAMS/Car and MATLAB showed that both of the optimal routes input were in tangent with the road boundary. We can observe through the longitudinal velocity that the MATLAB simulation results are more similar to a straight line than that of the ADAMS/Car simulation results, which meet the psychological expectation of a driver. Thus, the inverse dynamics model on minimum time handling of the vehicle is reasonable and feasible.